Carotid intima-media thickness as a surrogate marker of cardiovascular disease in diabetes - Sibal, Latika (Dove Medical Press, 2011)
BACKGROUND: Diabetes mellitus is associated with a high risk of cardiovascular disease. Carotid intima-media thickness (CIMT) is increasingly used as a surrogate marker for atherosclerosis. Its use relies on its ability to predict future clinical cardiovascular end points. METHODS: This review examines the evidence linking CIMT as a surrogate marker of vascular complications in people with type 1 and type 2 diabetes. We have also reviewed the various treatment strategies which have been shown to influence CIMT. CONCLUSIONS: CIMT measurement is an effective, noninvasive tool which can assist in identifying people with diabetes who are at higher risk of developing microvascular and macrovascular complications. It may also help to evaluate the effectiveness of various treatment strategies used to treat people with diabetes.